Pengaruh Loyalitas Dan Lifestyle Dalam Keputusan Pembelian Sepatu Nike (Studi Kasus Summarecon Mall Bekasi) - Munjir, Fhaisal Haris; Salim Siregar (Universitas Muhammadiyah Metro, 2024)
The purpose of this study was to determine how lifestyle and loyalty affected people'sdecisions to buy Nike sneakers at Summarecon Mall in Bekasi. This research uses multiplelinear regression analysis as part of the quantitative methodology approaches. Through thedistribution of questionnaires and the evaluation of factors connected to current variables,the data used in this study was collected. According to the study's findings, customer loyaltysignificantly and favorably influences their decision to buy Nike sneakers. The largestindicators are high quality and a well-known brand image; lifestyle does not, however,possess a favorable and noteworthy impact on the choices made by customers to buy Nikesneakers, the lowest indicator is